Gandhi and bin Laden:: Religious Conflict at the Polar Extremes - Rowell, James (Journal of Conflict Studies, 2006)
Abstract The current conflict of political terror advocated by religious Islamists, such as Osama bin Laden, threaten to eclipse the relevance of non-violent strategies advocated by Mohandas Gandhi and Martin Luther King Jr. An examination of the relative strengths and weakness of the tactics of non-violence (ahimsa) and violence (jihad) will show some short-term advantages for violence, that are serious ly mitigated by other long-term and tactical weaknesses. This investigation also suggests new ways (a chemical model) for understand ing the moral polar extremes of religious belief represented by Gandhi and bin Laden.